Biomarkers for antidepressant efficacy of electroconvulsive therapy: an exploratory cerebrospinal fluid study - Kranaster, Laura; Hoyer, Carolin; Aksay, Suna Su; Bumb, Jan Malte; Ozbalci, Cagakan; Janke, Christoph; Thiel, Manfred; Sartorius, Alexander (Neuropsychobiology, 2018)
Background: No candidate biomarkers based on cerebrospinal fluid (CSF) have been identified as prognostic factors in patients with major depression treated with electroconvulsive therapy (ECT), yet. Method: Following different underlying hypotheses, we analysed baseline CSF levels of markers of neurodegeneration (tau proteins, β-amyloids and neurogranin), elements of the innate immune system (interleukin [IL]-6, neopterin, soluble CD14, soluble CD163, migration inhibitory factor and monocyte chemotactic protein 1), endocannabinoids, sphingolipids and Klotho before ECT in patients with depression (n = 12) to identify possible correlations with the clinical antidepressant response to ECT. Results: Correlation with the reduction of the depressive symptoms could be observed especially for markers of neurodegeneration and elements of the innate immune system. Differences for CSF levels of several markers were found between the groups of responders and non-responders at the trend level. Limitations: The sample size is small and the distribution of responders and non-responders is uneven. Conclusions: It is this first study on CSF biomarkers for antidepressant efficacy of ECT warrants further research regarding the mechanism of ECT and personalized antidepressant therapy.
Gesehen am 24.03.2021